Sex disparities revealed by single-cell and bulk sequencing and their impacts on the efficacy of immunotherapy in esophageal cancer - Huimeng Yan; Jinyuan Huang; Yingying Li; Bin Zhao (Biology of Sex Differences, 2024)
Abstract Background There is an ongoing debate on whether sex affects immune-suppressive tumor microenvironment and immunotherapy. Here, we explored the underlying molecular bases for sex dimorphisms and their impact on the efficacy of immunotherapy in esophageal cancer (EC). Methods 2360 EC patients from phase 3 trials were pooled to compare overall survivals by calculating hazard ratios (HRs) and their 95% confidence intervals (CIs). Genomic data of 1425 samples were integrated to depict the genomic landscapes and antigenic features. We also examined the sex disparities based on single-cell RNA sequencing and T cell receptor-sequencing data from 105,145 immune cells in 60 patients. Results Immunotherapy was associated with favorable outcomes in men (HR, 0.71; 95% CI, 0.65–0.79; P < 0.001), but not in women (HR, 0.98; 95% CI, 0.78–1.23; P = 0.84) (P interaction =0.02). The frequencies of 8 gene mutations, 12 single base substitutions signatures, and 131 reactome pathways were significantly different between male and female. Additionally, six subtypes of HLA-II antigens were enriched in women. Hence, we constructed and then validated a sex-related signature to better predict the outcomes of immunotherapy. Exhausted CD8+ T cells were highly infiltrated in men, while naïve CD8+ T cells were more common in women. Further examinations on multiple malignancies suggested exhausted CD8+ T cells were enriched in patients who responded to immunotherapy. Conclusions Our study delineated the robust genomic and cellular sex disparities in EC. Furthermore, male, rather than female, derived significantly benefits from immunotherapy. These results have implications for treatment decision-making and developing immunotherapy for personalized care. Plain English Summary In the past several years, immunotherapy has gradually replaced the traditional chemotherapy as the standard treatment in esophageal cancer. It is well-established that immunological responses in male and female differ significantly. However, there is an ongoing debate on whether sex can impact the treatment outcomes in immunotherapy. In the present study, we systematically characterized the genomic and cellular landscapes of esophageal cancer, and revealed the significant differences between male and female patients. Furthermore, with over 2000 patients with esophageal cancer, we showed that only men can benefit from immunotherapy. In women, immunotherapy failed to show superior over chemotherapy. These results have implications for treatment decision-making and developing next-generation immunotherapy for personalized care.